Patient Activation as a Pathway to Shared Decision-making for Adults with Diabetes or Cardiovascular Disease - Poon, Bing Ying (J Gen Intern Med, 2019)
BACKGROUND: Shared decision-making (SDM) is widely recognized as a core strategy to improve patient-centered care. However, the implementation of SDM in routine care settings has been slow and its impact mixed. OBJECTIVE: We examine the temporal association of patient activation and patients’ experience with the SDM process to assess the dominant directionality of this relationship. DESIGN: Patient activation, or a patients’ knowledge, skills, and confidence in self-management, was assessed using the 13-item Patient Activation Measure (PAM). Patient-reported assessment of the SDM process was assessed using the 3-item CollaboRATE measure. Patients at 16 adult primary care practices were surveyed in 2015 and 2016 on PAM (α = 0.92), CollaboRATE (α = 0.90), and demographics. The relationship between PAM and CollaboRATE was estimated using a cross-lagged panel model with clustered robust standard errors and practice fixed effects, controlling for patient characteristics. PARTICIPANTS: 1222 adult patients with diabetes and/or cardiovascular disease with survey responses at baseline (51% response rate) and a 1-year follow-up (73% response rate). RESULTS: PAM (mean 3.27 vs 3.28 on a range of 1 to 4; p = 0.082) and CollaboRATE (mean 3.62 vs 3.63 on a range of 1 to 5; p = 0.14) did not change significantly over time. In adjusted analyses, the path from baseline PAM to follow-up CollaboRATE (β = 0.35; p < 0.0001) was stronger than the path from baseline CollaboRATE to follow-up PAM (β = 0.04; p = 0.001). CONCLUSIONS: The relationship between patient activation and patients’ experiences of the SDM process is bidirectional, but dominated by baseline patient activation. Rather than promoting the use of SDM for all patients, healthcare organizations should prioritize interventions to promote patient activation and engage patients with relatively high activation in SDM interventions.